Challenges to groundnut value chain development: Lessons from an (attempted) experiment in Ghana - Posey, Sean; Magnan, Nicholas; McCullough, Ellen B.; Hoffmann, Vivian; Opoku, Nelson; Alidu, Abdul-Hafiz (Informa UK Limited, 2024)
In developing countries, value chains for many crops are underdeveloped, leading to low producer prices and poor quality produce. Value chain research using secondary data is made difficult by selection problems, whereas experimental research is logistically very difficult and lacks external validity. With the intention of conducting a field experiment, we piloted an intervention connecting smallholder groundnut farmers in Ghana to a premium groundnut processor through aggregators. While we successfully delivered inputs and training to farmers, we failed in our attempts to link aggregators with downstream processors over two growing seasons. In this paper, we situate the challenges we faced in the broader literature on value chains and identify three problems that prevented us from establishing a value chain for high quality groundnuts: uncertainty, cash constraints, and trust. To help inform future research on this topic, we propose three specific interventions that could mitigate these problems.